Bargaining with Arrival of New Traders - Fuchs, William; Skrzypacz, Andrzej (American Economic Review, 2010)
We study dynamic bargaining with asymmetric information and arrival of exogenous events, which represent arrival of traders or information. We characterize the unique limit of stationary equilibria with frequent offers. The possibility of arrivals changes equilibrium dynamics. There is delay in equilibrium, and the seller slowly screens out buyers with higher valuations. The seller payoff equals what he can achieve by simply awaiting an arrival. In applications, when buyer valuations fall, average prices drop and delay increases. Surplus division depends on relative arrival rates of buyers/sellers and expected time to trade is a nonmonotonic function of the arrival rate. (JEL C78, D82)